Pengaruh Faktor Pribadi dan Keluarga terhadap Keberhasilan Relokasi Pegawai Direktorat Jenderal Perbendaharaan dengan Moderasi Dukungan Organisasional - Wibowo, Aji; Susilowati, Christin (Jurnal Aplikasi Manajemen, 2016)
This study was conducted to determine the effect of personal factors, family factors and organizational support on the successes of the relocation. The survey was given to 90 employees of the Directorate General of Treasury who has a family and has been relocated outside Java for more than a year. 76 respondents provide feedback through google forms and analyzed using the SmartPLS 2.0.M3 version. Personal factors and organizational support is proven to affect the successes of the relocation positively, whereas family factors did not affect the successes of the relocation. Moreover, the interaction between personal factors and organizational support can also affected the successes of the relocation, but negatively.